2006
DOI: 10.1093/humupd/dml009
|View full text |Cite
|
Sign up to set email alerts
|

Protamines and male infertility

Abstract: Protamines are the major nuclear sperm proteins. The human sperm nucleus contains two types of protamine: protamine 1 (P1) encoded by a single-copy gene and the family of protamine 2 (P2) proteins (P2, P3 and P4), all also encoded by a single gene that is transcribed and translated into a precursor protein. The protamines were discovered more than a century ago, but their function is not yet fully understood. In fact, different hypotheses have been proposed: condensation of the sperm nucleus into a compact hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
548
2
26

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(602 citation statements)
references
References 323 publications
4
548
2
26
Order By: Relevance
“…It has been shown that sperm with protamine deficiency and increased histone remnants, lead to premature chromatin condensation that is the cause of failures in fertilization and embryo development [16,33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that sperm with protamine deficiency and increased histone remnants, lead to premature chromatin condensation that is the cause of failures in fertilization and embryo development [16,33].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of proper DNA packaging in sperm has been associated with infertility in mice [160]. During the chromatin re-packaging in spermatogenesis process, about 85 % of the histones are replaced by protamines [161]. In the initial stages of spermiogenesis, histones are hyper acetylated and undergo other modifications [162].…”
Section: Epigenetic Modifications and Male Infertilitymentioning
confidence: 99%
“…Genetic causes of azoospermia in humans include chromosomal abnormalities, e.g., Y-chromosome microdeletions and mutations in specific genes; e.g., DAZ, SYCP3, PRM1, SPATA16, AURKC and KLHL10 [1][2][3][4][5][6][7]. As Y-chromosome deletions account for only 16% of men with infertility [8], azoospermia in many infertile men may be caused by mutations in autosomal genes.…”
Section: Introductionmentioning
confidence: 99%